Genetic Risk of Talon Cusp: Talon Cusp in Five Siblings - Nuha Abdel-Rahman Elmubarak (Case Reports in Dentistry)
Talon cusp is a rare dental anomaly that appears as a cusp-like projection on anterior teeth. Although numerous articles considering this anomaly have been published, this report has displayed a unique presentation of talon cusp. This case series is the first report in literature on which talon cusp has been presented in multiple siblings which highlights the genetic/familial component of the etiology. The report has also displayed unfamiliar morphological appearance (heart shape) of the talon cusp. Furthermore, talon cusp has shown an association with taurodontism in this report. Taurodontism has never been mentioned in the previous literature among the odontogenic variations that may associate talon cusp. A 25-year-old male has presented with talon cusps on the palatal surface of anterior teeth. Family history revealed four of his siblings had the same anomaly on anterior teeth. Talon cusps in the five cases cause clinical problems like occlusal interference, displacement and proclination of the anterior tooth, caries in the grooves delineating talon cusp, or pulp necrosis. Free dental treatment has been offered in the university clinic. However, they live in remote rural areas making it difficult to follow up with treatment.